Intimate Partner Violence Among Low-Income Fathers: Testing a Stress-Coping Model. Issue 3 (February 2021) - Gordon, Derrick M.; Moore, Kelly E.; Vincent, Wilson; Iwamoto, Derek K.; Campbell, Christina; Hunter, Bronwyn A.; Ward, Nadia L.; Hawes, Samuel W.; Albritton, Tashuna; McCaulley, Horace; DiTunno, Dianna; Judkins, Anthony
This research used a stress-coping conceptual framework to examine intimate partner violence (IPV) among men who are fathers. The current study examined how perceived stress explained associations between stressors (e.g., employment status, psychological and physical female-to-male partner violence [FMPV], substance use, criminal justice system involvement) and male-perpetrated physical and psychological IPV. Participants were 1, 971 low-income, ethnically diverse fathers involved in a statewide fatherhood program. Findings indicated that, across African American, White, and Hispanic/Latino men, male-reported FMPV and criminal justice involvement were associated with psychological and/or physical IPV via perceived stress. Employment status and alcohol use were associated with psychological IPV via perceived stress among African American men only. Implications for community-based fatherhood programs are discussed.